Challenges of social safety nets in Indonesia - Jamaruddin Suro (Journal of Research and Multidisciplinary, 2018)
Social safety nets (SSNt) is a form of government involvement in providing assistance to need a life of the poor and vulnerable for increasing the quality of life people. This study is an introduction that discusses the concept and program of SSNt among fishermen in South Sulawesi Province. How SSNt interests and challenges in improving people's quality of life.